The structure of a protein primer–polymerase complex in the initiation of genome replication - Ferrer-Orta, Cristina (2006)
Picornavirus RNA replication is initiated by the covalent attachment of a UMP molecule to the hydroxyl group of a tyrosine in the terminal protein VPg. This reaction is carried out by the viral RNA-dependent RNA polymerase (3D). Here, we report the X-ray structure of two complexes between foot-and-mouth disease virus 3D, VPg1, the substrate UTP and divalent cations, in the absence and in the presence of an oligoadenylate of 10 residues. In both complexes, VPg fits the RNA binding cleft of the polymerase and projects the key residue Tyr3 into the active site of 3D. This is achieved by multiple interactions with residues of motif F and helix α8 of the fingers domain and helix α13 of the thumb domain of the polymerase. The complex obtained in the presence of the oligoadenylate showed the product of the VPg uridylylation (VPg-UMP). Two metal ions and the catalytic aspartic acids of the polymerase active site, together with the basic residues of motif F, have been identified as participating in the priming reaction.